Seminários em Bio-Matemática - Braumann, Carlos A. (2008)
Seminários de Bio-matemática, Universidade Estadual de Campinas, Brazil, Dec 11, 2007. Invited seminar on modelling of population growth and fishing in random environments, part 2.